Common Ayurvedic, Chinese traditional and Unani antidiabetic formulations- a review - Murudkar, Prajakta H.; Tambe, Mukul S.; Chandrasekar, S.B.; Boddeda, Bhavani; Pawar, Anil T. (Frontiers in Pharmacology, 2022)
Diabetes mellitus is the most widely recognized endocrine disorder which is influencing a bigger populace on the planet. There are various causes of diabetes, such as physical inactivity, obesity, family history, race, and age. Diabetes mellitus is associated with some life-threatening complications, such as neuropathy, nephropathy, various eye diseases or retinopathy, and cardiovascular disorders. Many synthetic antihyperglycemic agents are available in the market for the treatment of diabetes and its complications. But, due to some serious side effects of these synthetic agents, people are opting for herbal remedies and, therefore, they are now becoming popular. Herbal remedies have lesser side effects and higher affordability and therefore can be preferably used over synthetic agents for a long-term disorder like diabetes mellitus. In the present study, scientific research and review studies on the topic were collected from Science Direct, Scopus, PubMed, Google Scholar, and other relevant sources. The references of all the articles were screened manually for any additional information on popular polyherbal formulations in traditional Ayurvedic, Chinese, and Unani medicinal systems. It is found that these polyherbal formulations are studied for anti-diabetic potential. Furthermore, some are also investigated for mechanism of action of anti-diabetic effects. This review highlights various Ayurvedic, Chinese, and Unani polyherbal formulations commonly utilized in the management of diabetes mellitus along with their pre-clinical and clinical investigations, which will enhance the existing knowledge of the researchers.